Magnesium-Assisted Cisplatin Inhibits Bladder Cancer Cell Survival by Modulating Wnt/β-Catenin Signaling Pathway - Li, Tianye; Tang, Zihan; Li, Chunting; Liu, Xiaoya; Cheng, Linglin; Yang, Zhijing; Zhu, Xiaojin; Liu, Weiwei; Huang, Yongye (Frontiers in Pharmacology, 2022)
Magnesium, an essential mineral micronutrient, plays a role in the activation of various transporters and enzymes. The present study aimed to investigate the possibility of applying magnesium to enhance the efficacy of cisplatin which is still ranked as one of the major chemotherapeutic drugs for bladder cancer patients. Results showed that the survival rate and colony formation of bladder cancer cells were reduced by combinatorial treatment with cisplatin and magnesium chloride (MgCl2). The proportion of apoptotic cells was also increased in UC3 bladder cancer cells treated with a combination of cisplatin and MgCl2. Most importantly, a marked decrease in nuclear β-catenin was observed in cells that received cisplatin treatment. In addition, the nuclear β-catenin in cisplatin treated cells was further down-regulated by supplementing MgCl2. 6-bromoindirubin-3'-oxime (BIO), an inhibitor of glycogen synthase kinase-3 (GSK-3) that activates the Wnt/β-catenin signaling pathway by modulating β-catenin activity, was thus applied to further exploit the role of this signaling pathway in magnesium aided cancer treatment. The survival rate of bladder cancer cells was decreased by BIO treatment at concentrations of 1.0, 2.5 and 5.0 μM accompanied by increased β-catenin expression. However, the expression of β-catenin in MgCl2-treated cells was lower than in untreated cells under the same BIO concentration. The expression of cleaved caspase-3, cleaved caspase-9 and microtubule-associated protein 1 light chain 3- II (LC3-II) was highest in cells treated with MgCl2 and 5.0 μM BIO among the examined groups. Our findings reveal that magnesium could contribute to cisplatin-based chemotherapy by moderately regulating the Wnt/β-catenin signaling pathway.